IMUNOHISTOKIMIA PADA KONDILOMATA AKUMINATA - Widyaswari, Meidyta Sinantryana; Lumintang, Hans; Soemarno, Troef (Jurnal Ilmu Kesehatan dan Kesehatan, 2019)
Background: Condylomata Acuminata (CA) is a sexually transmitted disease caused by the Human Papilloma Virus (HPV) type-specific and may be simultaneously co-infected with other HPV types associated with malignancy. Purpose: To differentiate between CA and histopathological of malignancy by immunohistochemistry. LiteratureReview: CA refers to benign epidermal proliferation caused by the HPV types 6 and 11, but co-infection with high- risk HPV types are common. The clinical presentation of CA can’t differentiate between benign or preneoplastik diplasia lesions. Koilocytes considered pathognomonic for HPV lesions, these findings sometimes don’t appear on CA, and histopathology was not accurate, that immunohistochemistry with MIB-1 (Ki-67) and p16 can beused. Conclusion: Immunohistochemistry examination can help differentiate the diagnosis between malignancy or non- malignancy in the case of CA.